Mapping the Literature on Sustainable Scale-up Strategies: A Bibliometric Review - Judijanto, Loso (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric review of the global scholarly landscape on sustainable scale-up strategies, employing VOSviewer to analyze publication trends, thematic clusters, and collaborative networks. Data were sourced from the Scopus database, covering journal articles, reviews, and conference papers published between 2000 and 2024. The co-authorship, country collaboration, and keyword co-occurrence analyses reveal that scale up, biomass, and wastewater treatment are central research themes, with strong linkages to governance, cost-benefit analysis, environmental impact, and emerging sustainability concepts such as the circular economy. Temporal overlay mapping indicates a thematic shift from early dominance of health-related scaling—focusing on healthcare systems, programs, and quality—towards more integrated approaches encompassing climate action, renewable energy, and resource efficiency. The density visualization further highlights high-intensity research areas while showing the multidisciplinary nature of the field, bridging environmental technology, socio-economic policy, and public health. The findings provide valuable insights for researchers, policymakers, and practitioners, guiding strategic research agendas, fostering cross-sector collaboration, and informing evidence-based policy to achieve scalable and sustainable solutions.